Marathon pacing ability: Training characteristics and previous experience. Issue 7 (8th August 2020) - Swain, P.; Biggins, J.; Gordon, D.
Abstract : Even pacing within the marathon has been associated with faster marathon performance times, however, little literature has investigated the association between pacing ability during a marathon and a recreational marathoner's training characteristics and previous experiences. N = 139 participants completed an online questionnaire concerning training history in relation to a 2017 marathon and previous long-distance running experiences. Online databases were used to collect split times of the participants after successfully completing a 2017 marathon, identifying the percentage slowdown in pace between the first half and second half of the marathon, used for correlational analyses. The strongest correlates for pacing ability were marathon finishing time and previous distance race personal best finishing times (i.e. marathon, half-marathon, 10 and 5 km). There were many weaker, however significant correlates for training history characteristics and previous long-distance running experience. The current findings demonstrate that greater accrued long-distance running experiences and higher weekly training volumes are strongly associated with smaller declines in pace during the second half of the marathon in comparison to the first half and less variability in pace during the marathon.